Update on Adjuvant Chemotherapy for Early Breast Cancer. (January 2014) - Rampurwala, Murtuza M.; Rocque, Gabrielle B.; Burkard, Mark E.
Breast cancer is the second most common cancer in women worldwide. Although most women are diagnosed with early breast cancer, a substantial number recur due to persistent micro-metastatic disease. Systemic adjuvant chemotherapy improves outcomes and has advanced from first-generation regimens to modern dose-dense combinations. Although chemotherapy is the cornerstone of adjuvant therapy, new biomarkers are identifying patients who can forego such treatment. Neo-adjuvant therapy is a promising platform for drug development, but investigators should recognize the limitations of surrogate endpoints and clinical trials. Previous decades have focused on discovering, developing, and intensifying adjuvant chemotherapy. Future efforts should focus on customizing therapy and reducing chemotherapy for patients unlikely to benefit. In some cases, it may be possible to replace chemotherapy with treatments directed at specific genetic or molecular breast cancer subtypes. Yet, we anticipate that chemotherapy will remain a critical component of adjuvant therapy for years to come.